Hydrochemical behaviour of an underground dammed limestone aquifer in the subtropics. Issue 23 (25th September 2018) - Nakaya, Shinji; Yasumoto, Jun; Ha, Phan Min; Aoki, Hideto; Kohara, Fumiya; Masuda, Harue; Masuoka, Kentaroh
Abstract: In an island area with limited surface water resources, the conservation of fresh groundwater resources is important for the maintenance of the water supply and irrigation system to be used in agricultural activity. In a limestone aquifer used for irrigation on a subtropical island, the progress of the dissolution behaviour of the aquifer and the effects of CO2 storage and chemical weathering of the aquifer must be understood to ensure sustainable groundwater use. In this study, hydrochemical behaviour of the Ryukyu limestone aquifer was investigated using the residence time of slowly flowing groundwater, which is contained by a 2.3‐km‐long underground man‐made dam constructed in 2005 located at the southern edge of Okinawa Island, Japan. Groundwater dating and horizontal flow velocity measurements indicate that the groundwater horizontal flow is slow in the underground dam area, whereas the saturation index (SI) for calcite indicates that the majority of the limestone exists in a supersaturated condition. The range of SI for gypsum was indicative of subsaturation, and the SI increased with the groundwater residence time, suggesting that the dissolution of CaSO4 tends to proceed slowly through the common ion effect. The dissolution of CaCO3, however, tends to be in suspension within about a residence time of 20 years. The apparent dissolution rate of Ca in the Ryukyu limestone aquifer in this area was estimated to be approximately 2.70–4.06 nmol cm −2  year −1, a value much lower than that of the early stages of the limestone dissolution. The estimated groundwater CO2 (gas) concentrations are two order high (about 0.3–7%) relative to atmospheric CO2 (about 0.04%), and the groundwater pH shows a tendency to decrease from 7.4 to 6.9 over the last approximately 20 years, indicating that the hydration reaction of CO2 occurs in the Ryukyu limestone aquifer. These findings imply that high CO2 produced in the subtropical zone is consumed slower than CO2 production during limestone dissolution, with the exclusion of the early stage of the chemical weathering process, and causes groundwater acidification in the underground dammed limestone aquifer.